‘NOTHING ABOUT CRPD MONITORING WITHOUT US’: A CASE STUDY ON THE INVOLVEMENT OF THE DISABILITY MOVEMENT IN POLICY-MAKING IN ZAMBIA (African Disability Rights Yearbook, 2021)
Article 33 of the UN CRPD is the most comprehensive provision referring to national level implementation and monitoring ever included in an international human rights treaty. It requires states parties to establish a triangular mechanism comprising of government, an independent element and civil society, in particular organisations of persons with disabilities (DPOs), to handle and monitor the implementation of the Convention. Bearing in mind that the human rights model introduced in the CRPD shall be applied to a historically marginalised group, the fulfilment of this obligation is essential but also challenging. Nevertheless our knowledge is very limited on the criteria of effective involvement. This chapter intends to explore and identify some of the key factors of active and effective civil society participation in policy-making through the example of Zambia. The paper also discusses the financial challenges of a developing country when implementing and monitoring the UN CRPD. In Zambia the disability movement took the leading role and initiated the establishment of the Independent Monitoring Unit (IMU). Since the Human Rights Commission of Zambia – as the Paris Principle compliant independent body – does not actively participate in the work of the monitoring body, the Zambian solution to implement article 33 of the CRPD cannot be considered as a good practice. However, it is certainly an interesting case study on the empowerment and involvement of the organisations for persons with disabilities. It is important to consider how far we can take the principle ‘Nothing about us without us!’ to ensure the participation of the disability movement but also achieve compliance with the CRPD.
Keywords: UN; CRPD; policy-making; implementation; persons with disabilities; disability movement